Assessment of the channels of transmission of oil price fluctuations to the economy - Taghizadeh-Hesary, Farhad; Yoshino, Naoyuki (Wydawnictwo Uniwersytetu Ekonomicznego we Wrocławiu, 2018)
This paper develops a New Keynesian model to examine a theoretical global economy with two basic macroeconomic components: an energy1 producer and an energy consumer. This simple economy uses these two components to evaluate how oil prices affect the consumer economy’s gross domestic product and inflation. This model assumes that changes in the oil price transfer to macro variables through either supply (aggregate supply curve) or demand channels (aggregate demand curve). To examine the effects of this transfer, an Investment-Saving (IS) curve is used to look at the demand side and a Phillips curve is used to analyze the inflationary effects from the supply side. The empirical analysis concludes that movements in the oil price mainly affect the economy through the demand side (shifting the aggregate demand curve) by affecting household expenditures and energy consumption. This analysis provides several additional findings, among which is that easy monetary policies amplify energy demand more than supply, resulting in skyrocketing crude oil prices, which inhibit economic growth
Argumenta Oeconomica, 2018, Nr 2 (41), s. 5-34
Keywords: oil prices; New Keynesian model; IS curve; Phillips curve; monetary policy